EVALUACIÓN DEL VALOR NUTRICIONAL DE LA Puya llatensis EN LA ALIMENTACIÓN DEL CUY (Cavia porcellus) - Clemente J., Ever (2003)
The nutritional quality and digestibility in vivo of the Puya llatensis for cobayo feeding was evaluated. The chemical analysis indicated 87.2% humidity, 2.3% protein, 0.75% ether extract, 15.43% crude fiber, 70.43% nitrogen free extract, 11.07% ashes, 0.04% calcium and 0.38% phosphorus on dry base. Moreover, the content of ascorbic acid (Vitamin C) was 7.74 mg in 100 mg of fresh sample. A digestibility test was conducted on 10 male cobayos of 12 weeks of age and 650 g body weight. The coefficients of digestibility were: Dry matter (75.96%), total protein (28.86%), crude fiber (54.89%), ether extract (49.58%), nitrogen free extract (80.56%), and ashes (87.25%). For the feeding trial, 25 male cobayos of 30 days of age and 290 g body weight were used. Animals were distributed at random in five groups: T1 (control) = (barley + alfalfa 100%), T2 (barley + alfalfa 75% + Puya llatensis 25%), T3 (barley + alfalfa 50% + Puya llatensis 50%), T4 (barley + alfalfa 25% + Puya llatensis 75%), T5 (barley + Puya llatensis 100%). Body gain weight, feed intake and feed conversion were evaluated at three periods: initial (0-28 d), final (28-56 d), and total (0-56 d), and no statistical differences were found between T1, T2 and T3 groups (p>0.05). It was concluded that the use of Puya llatensis till levels of 50% alfalfa replacement do not affect the productive performance of cobayos.